Structural patterns in the marketing of selected agricultural products in Chile : the position of small and large growers - Fletschner, Carlos (Madison, Wisconsin Land Tenure Center, University of Wisconsin, 1971)
This book deals with Chile's sufficient food and other Agricultural product for her need.
Based on the author's thesis.
Includes bibliographical references.
oo 08/04/2019
Loans
Keywords: Farm produce; Agriculture